Role of the triple solute/ion/water interactions on the saccharide hydration: A volumetric approach. (7th August 2017) - Teychené, J.; Roux-De Balmann, H.; Galier, S.
Abstract: The aim of this study is to further the understanding of the mechanisms that govern the hydration behavior of neutral solutes, with respect to the ions' properties that are present in a solution. For that, a systematic volumetric study of saccharides (xylose, glucose and sucrose), in the presence of various electrolytes (LiCl, NaCl, KCl, Na2 SO4, K2 SO4, CaCl2, MgCl2, MgSO4 ) has been carried out with density measurements at 298.15 K. From this data, the standard transfer molar volume of the saccharide Δ V ϕ, S 0, which characterizes the hydration state of the solute, has been determined. Positive and increasing values of Δ V ϕ, S 0 with increasing electrolyte concentrations were obtained. This indicated the dehydration of the saccharide in the presence of the electrolyte, due to the predominance of saccharide/cation interactions. Concerning the influence of the cation, it was shown that saccharides are more dehydrated in the presence of divalent cations than in the presence of monovalent ones. This is because the interactions are stronger between saccharides and divalent cations, in comparison to those with monovalent cations. For a specific cation valence and molality, regardless of the anion, saccharide dehydration increases according to the following sequences: Li + < Na + < K + and Mg 2+ < Ca 2 + . These saccharide dehydration sequences have been explained by the Gibbs free energy of hydration of the cations, reflecting the cation/water interactions. For a specific cation valence, it was concluded that decreasing cation/water interactions induce the increase of saccharide dehydration. Concerning the influence of the anion, it was also observed that saccharides are more dehydrated in the presence of divalent anions than in the presence of monovalent ones. It was stated that saccharide/cation interactions are modulated by the nature of the anion. The anion impact was again attributed to its capacity to interact with water molecules. It was pointed out that anions with increasing values of Gibbs free energy of hydration cause an increase in saccharide/cation interactions or a decrease in saccharide/anion interactions. Therefore, saccharide dehydration increases. Graphical abstract: Relationship between the standard transfer partial molar volume of sucrose▲, glucose ■ and xylose ◊ and the Gibbs free energy of hydration of the cations (absolute value) for a cation molality mcation  = 1 mol kg −1 (monovalent cations): influence of the Gibbs free energy of hydration of the cations. Sulfate salts: empty symbols; Chloride salts: full symbols. Highlights: Saccharide standard transfer partial molar volumes are positive and increase with the electrolyte concentration. Saccharides are more dehydrated in presence of divalent cations than in presence of monovalent ones. The anions, Cl − or SO4 2−, have no influence on the cation-dependence order. Saccharide hydration is linked to the hydration Gibbs free energy of ions. Triple Solute/Ion/Water interactions are emphasised.